The F1Fo-ATP Synthase β Subunit Is Required for Candida albicans Pathogenicity Due to Its Role in Carbon Flexibility - Li, Shui-Xiu; Wu, Hao-Tian; Liu, Yu-Ting; Jiang, Yi-Ying; Zhang, Yi-Shan; Liu, Wei-Da; Zhu, Kun-Ju; Li, Dong-Mei; Zhang, Hong (Frontiers in Microbiology, 2018)
Previous work has explored links between mitochondrial biology and fungal pathogenicity in F1Fo-ATP synthase in Candida albicans. In this work we have detailed the more specific roles of the F1Fo-ATP synthase β subunit, a key protein subunit of F1Fo-ATP synthase. The ability to assimilate alternative carbons in glucose-limited host niches is known to be a critical factor for C. albicans infection. The function of the F1Fo-ATP synthase β subunit was characterized through the construction of an ATP2 gene null mutant (atp2Δ/Δ) and the gene-reconstituted strain (atp2Δ/ATP2) in order to understand the link between carbon metabolism and C. albicans pathogenesis. Cell growth, viability, cellular ATP content, mitochondrial membrane potential (ΔΨm) and intracellular ROS were compared between null mutant and control strain. Results showed that growth of the atp2Δ/Δ mutant in synthetic medium was slower than in complex medium. However, the synthetic medium delayed the onset of reduced cell viability and kept cellular ATP content from becoming fully depleted. Consistent with these observations, we identified transcriptional changes in metabolic response that activated other ATP-generating pathways, thereby improving cell viability during the initial phase. Unlike glucose effects, the atp2Δ/Δ mutant exhibited an immediate and sharp reduction in cell viability on non-fermentable carbon sources, consistent with an immediate depletion of cellular ATP content. Along with a reduced viability in non-fermentable carbon sources, the atp2Δ/Δ mutant displayed avirulence in a murine model of disseminated candidiasis as well as lower fungal loads in mouse organs. Regardless of the medium, however, a decrease in mitochondrial membrane potential (ΔΨm) was found in the atp2Δ/Δ mutant but ROS levels remained in the normal range. These results suggest that the F1Fo-ATP synthase β subunit is required for C. albicans pathogenicity and operates by affecting metabolic flexibility in carbon consumption.